Repositioning tolcapone as a potent inhibitor of transthyretin amyloidogenesis and associated cellular toxicity - Ricardo Sant'Anna (Nature Portfolio, 2016)
Misfolding of transthyretin can cause amyloid aggregation disorders that can be treated by stabilizing the tetrameric form with tafamidis. Here the authors show that tolcapone, a drug already FDA-approved for Parkinson disease, has strong transthyretin stabilizing function and might be a superior therapeutic option for CNS amyloidosis as it can cross the blood brain barrier.